Koalisi partai politik terhadap munculnya calon Tunggal pada Pilkada 2024 - Septica Sisilia; Suryanef Suryanef; Al Rafni; Irwan Hamdi (Journal of Education, Cultural and Politics, 2026)
The emergence of a single candidate in the 2024 Regional Head Election in Dharmasraya Regency creates a dilemma between political parties’ interests in securing electoral victory and the democratic principle of fair political competition. This study aims to analyze the factors influencing the nomination of a single candidate from both internal and external perspectives of political parties, as well as its implications for public trust. This research employs a qualitative approach with a descriptive case study method. Data were collected through in-depth interviews, documentation, and literature review involving political party representatives, election organizers, and the community. The findings indicate that the emergence of a single candidate is influenced by centralized decision-making at the national party level, pragmatic political strategies, weak party cadre development, high political costs, candidate electability, and nomination threshold regulations. These conditions have led to decreased public enthusiasm and trust, although some citizens continue to participate as a form of democratic responsibility. These findings suggest that the quality of democracy has not been fully optimized, particularly in terms of political competition and representation.